2014
DOI: 10.5539/jmbr.v4n1p34
|View full text |Cite
|
Sign up to set email alerts
|

Extended Spectrum Beta- Lactamase- Producing Uropathogenic Escherichia coli in Pregnant Women Diagnosed With Urinary Tract Infections in South-Western Nigeria

Abstract: Extended spectrum beta-lactamase (ESBL)-producing uropathogenic Escherichia coli (UPEC) in symptomatic pregnant women with confirmed urinary tract infections in Southwest. Nigeria was reported. Susceptibility of UPEC isolates to β-lactam and other classes of antibiotics was determined by the Kirby-Bauer's disc diffusion method on Mueller-Hinton agar plate. Detection of plasmid DNA in multiple antibiotic resistant isolates was carried out by alkali lysis (TENS) method. Extended-spectrum-β-lactamase (ESBL) produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
2
7
1
Order By: Relevance
“…Moreover, some isolates from male and female were resistant to 10 out of 11 antibiotics. This observation is similar to the work carried out by Oluduro et al [25]. According to the work, high prevalence of MDR strains was obtained.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, some isolates from male and female were resistant to 10 out of 11 antibiotics. This observation is similar to the work carried out by Oluduro et al [25]. According to the work, high prevalence of MDR strains was obtained.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of ESBL‐positive E coli isolates was higher in patients with AB (33%, 95% CI 21, 45%) than in pregnant women diagnosed by symptomatic UTI (16%, 95% CI 8, 24%). The prevalence estimate was 6% (95% CI 0, 12%) in three studies with high quality and it was 20% (95% CI 11, 29%) in seven studies with low quality . Considering the results of investigation for reporting bias, the Begg's ( Z = 1.43; P = .15) and Egger's tests (bias = −2.21; P = .07) results demonstrated that this bias is ignorable.…”
Section: Resultsmentioning
confidence: 87%
“…Ten studies (two from Africa, four from Asia and four European studies) investigated ESBL production by E coli isolates among pregnant women with UTIs 18,47,[60][61][62][63][64][65] ; Tables 3 and 4. The pooled prevalence of ESBL-P E coli isolates was 17% (95% CI 9, 24%), I 2 = 88.27%; Figure 5.…”
Section: Subset Of Primary Studies That Investigated Only E Coli Ismentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies (Nelson et al, 2014;Olufunke et al, 2014;Aljabri et al, 2010;Bebell et al, 2017;Tito et al, 2017), detected ESBL production using the double disc synergy test (DDST).…”
Section: Detection and Confirmation Of Esbl In The Laboratory: What Mmentioning
confidence: 99%